Clinical relevance of genetic polymorphisms in WNT signaling pathway (SFRP1, WNT3A, CTNNB1, WIF-1, DKK-1, LRP5, LRP6) on pulmonary tuberculosis in a Chinese population - Huang, Qian; Wang, Chao-Cai; Liu, Yun-Guang; Zhao, Chang-Ming; Zhang, Tian-Ping; Liu, Yan; Wang, Hua (Frontiers in Immunology, 2022)
The present study was performed to evaluate the association of WNT signaling pathway genes variants with pulmonary tuberculosis (PTB) risk in Chinese Han population. Our study subjects were composed of 452 PTB patients and 465 normal controls, and seventeen SNPs of seven genes in WNT signaling pathway (SFRP1, WNT3A, CTNNB1, WIF-1, DKK-1, LRP5, LRP6) were genotyped by SNPscan technique. We found no significant relationship of SFRP1 rs10088390, rs4736958, rs3242, WNT3A rs752107, rs3121310, CTNNB1 rs2293303, rs1798802, rs4135385, WIF-1 rs1026024, rs3782499, DKK-1 rs2241529, rs1569198, LRP5 rs3736228, rs556442, LRP6 rs2302685, rs11054697, rs10743980 polymorphisms with PTB susceptibility. While, WIF-1 rs3782499 variant was associated with susceptibility to PTB under recessive model, and haplotype analysis showed that DKK-1 GA haplotype frequency was significantly increased in PTB patients. The WNT3A rs3121310, CTNNB1 rs2293303 polymorphisms were respectively associated with drug-induced liver injury (DILI), sputum smear-positive in PTB patients. The rs3782499 in WIF-1 gene was related to fever, leukopenia, and the rs1569198 in DKK-1 was linked to sputum smear-positive in PTB patients. In LRP5 gene, rs3736228, rs556442 variants respectively affected the occurrence of DILI, fever, and LRP6 gene rs2302685, rs10743980 variants respectively influenced the development of hypoproteinemia, sputum smear-positive in PTB patients. Our results revealed that WNT signaling pathway genes variation were not associated with the susceptibility to PTB, while WNT3A, CTNNB1, WIF-1, DKK-1, LRP5, LRP6 genetic variations might be closely related to the occurrence of several clinical characteristics of PTB patients.